IMPLEMENTASI PERDA RTRW KOTA MEDAN TAHUN 2022 DAN IMPLIKASIINYA TERHADAP PENGEMBANGAN INFRASTRUKTUR UNDERPASS HM YAMIN KECAMATAN MEDAN TIMUR - Eleocetrin Manalu; Jhonson Pasaribu; Kepler Sinaga; Maringan Panjaitan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the implementation of Medan City Regional Regulation Number 1 of 2022 on Spatial Planning in the development of the H.M. Yamin Underpass infrastructure and its implications for transportation accessibility in Medan Timur District, Medan City. This research uses a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation. The analysis applies the policy implementation theory of George C. Edward III, which includes communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of the spatial planning regulation, as evidenced by the development of the H.M. Yamin Underpass, has improved traffic flow and community mobility. However, the implementation has not been fully optimal due to challenges in inter-agency coordination and policy communication with the community. The development of the underpass has improved transportation accessibility in Medan Timur, although further integration with the urban transportation system in Medan City is still required.